Determinants of economic growth in small states - Armstrong, Harvey W. (2003)
Addresses the issue of small economic size and outlines the principal economic constraints on the growth of small states as a consequence of their sub-optimality. Discusses the vulnerability of small states and their greater exposure to exogenous shocks because of their size. Provides an extensive review of the empirical findings on the determinants of growth in small states. Summarizes the key policy implications and policy lessons for small states in the face of globalization.